Influence Of Marketing Influencer , Online Customer Reviews And Product Quality On Purchasing Decisions For Skintific Products On Tiktok Platform - Shaafi Abidah; Mochamad Rizal Yulianto; Muhammad Yani (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study analyzes the influence of influencer marketing, online customer reviews, and product quality on Skintific's purchasing decisions on TikTok. Methodology: This study uses a descriptive quantitative design with purposive sampling of 140 respondents. The data were analyzed using SmartPLS through Outer Model Test, Cronbach's Alpha, AVE, Composite Reliability, R², and path coefficient estimation. Results: The results show that Marketing through Influencers has a positive effect on Purchase Decisions (T = 3.210, p = 0.001) and increases consumer trust and buying interest. Online Customer Reviews also have a positive effect on Purchase Decisions (T = 2.950, p = 0.003). Product Quality has a positive effect on Purchase Decisions (T = 4.110, p = 0.000).Findings: This study shows that influencer marketing, online customer reviews, and product quality positively affect Skintific's purchasing decisions on TikTok, with product quality and customer reviews being the main factors. Novelty: This study provides new empirical contributions to TikTok digital marketing, showing the synergy between influencers, customer reviews, and product quality as key factors in purchasing decisions. Originality: This research focuses on the influence of these three variables and TikTok's role as a primary marketing platform for Skintific products. Conclusion: Influencer marketing, online customer reviews, and product quality have a significant positive effect on Skintific purchasing decisions on TikTok. Integrating these three variables can increase trust, loyalty, and sales. Type of Paper: Empirical research paper.